Neighborhood Social Ties and Informal Social Control: when do Neighbors Call the Police or Directly Intervene? - Cwick, Jaclyn M. (Criminology, criminal justice, law & society, 2022)
Social disorganization theory posits that neighborhood social ties facilitate residents’ engagement in distinct forms of informal social control important for crime reduction, including private, parochial, and public controls (Bursik & Grasmik, 1993). Yet research examining how social ties contribute to various forms of informal social control is rare, despite a recent resurgence in efforts to clarify these measures (see Warner, 2014). The present study examines whether neighborhood social ties influence direct informal social control (i.e., residents’ perceptions that their neighbors will stop a crime themselves or will get another neighbor to help) and indirect informal social control (i.e., residents’ perceptions that their neighbors will call the police) within ordinary least squares regression. Findings indicate that previous studies, which have relied on global measures of informal social control, have concealed more nuanced relationships regarding social ties and forms of informal social control. More specifically, neighborhood social ties were positively related to direct informal social control at low levels of disadvantage, but were negatively related to direct informal social control in neighborhoods with high concentrated disadvantage, while social ties were positively related to indirect informal social control regardless of disadvantaged context. Findings point to the importance of including more specific measures of informal social control in current and future residential surveys.